Oporto Centenarian Study - Ribeiro, Oscar (2016)
This entry presents the first population-based study conducted in Portugal, the Oporto Cente- narian Study (PT100). It starts by providing an overview of the centenarian population in Portu- gal and then describes PT100’s methodological approach (sampling, procedures, and measures) and synthesizes its main findings on three core dimensions considered to be determinants of qual- ity of life in extreme old age (Serra et al. 2011): cognitive and physical functioning, social resources (social relationships and social activi- ties), and personal attitude toward life (valuation of life). An outlook of current satellite projects of the PT100 is presented at the end.